PENGARUH PENGGUNAAN INFORMASI AKUNTANSI TERHADAP USAHA MIKRO KECIL MENENGAH (UMKM) - Riska Amalia (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
The development of the business world today is very fast side by side with the development of technology, in supporting the success of a business, the role of accounting is very much needed. This study aims to determine the effect of using accounting information on micro, small and medium enterprises. The object of this research is a small micro business engaged in socks in the city of Bandung. The data obtained in the study through observation, interviews, and documentation studies. The results obtained in the study are the conclusions drawn by the author that the use of information has a positive influence on the success of a business.